Uric acid and cardiovascular disease - Guimarães, Joana (2004)
The interest in serum uric acid as a potential Cardiovascular Disease risk factor has balloned in the last several years with numerous review articles. There seems little doubt that serum uric acid is a risk factor for Cardiovascular Disease, a perception that has persistfor nearly 50 years. However, the central issue is not whether uric acid is associated with Cardiovascular Disease, but whether uric acid plays a causal role in the development of Cardiovascular Disease.It has been diffi cult to identify the specific role of elevated serum uric acid because of its association with established cardiovascular risk factors such as Hypertension, Diabetes Mellitus, Hyperlipidaemia and Obesity.Increased understanding of the mechanisms underlying these associations may allow a clearer interpretation of the importance of elevated serum uric acid concentration.